2016
DOI: 10.1007/978-3-319-38980-6_25
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Software Development Process Terminology

Abstract: Abstract. The practice of software development has evolved considerably in recent decades, with new programming technologies, the affordability of hardware, pervasive internet access and mobile computing all contributing to the emergence of new software development processes. The newer process initiatives, which include those which are sometimes referred to as agile or lean methods, have brought with them new terms, which sometimes reflect the introduction of novel concepts. Other times, new terms correspond t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…Earlier work from the authors has examined the potential for a latent terminology problem to exist in the software engineering field [14] We found that within software engineering, there is strong evidence to suggest that a terminology problem has arisen, and we have advocated that this problem could be tackled through the use of ontology [15]. We have also seen that this terminology concerns extends to role definition [16].…”
Section: Potential Situation Impact and Discussionmentioning
confidence: 88%
“…Earlier work from the authors has examined the potential for a latent terminology problem to exist in the software engineering field [14] We found that within software engineering, there is strong evidence to suggest that a terminology problem has arisen, and we have advocated that this problem could be tackled through the use of ontology [15]. We have also seen that this terminology concerns extends to role definition [16].…”
Section: Potential Situation Impact and Discussionmentioning
confidence: 88%
“…And this task of researching the available process alternatives must be frustrated by the fragmented process terminology, where in previous basic research we have found that individual concepts can be branded using many different terms [30][31]. Yet ironically, an absence of attention to the various available techniques could be damaging to the success of any given firm.…”
Section: Discussionmentioning
confidence: 99%
“…), Systems, Software and Services Process Improvement: 24th European Conference, EuroSPI 2017, Ostrava, Czech Republic, , Proceedings (pp. [29][30][31][32][33][34][35][36][37][38][39][40][41][42]. Cham: Springer International Publishing.…”
Section: Introductionmentioning
confidence: 99%
“…However, on the evidence of our initial research, it would appear that the software process domain suffers from an inconsistent use of terminology, to the extent that there may be large latent terminology problem concerning software development activities and roles [4]. That a terminology problem exists in our domain may to some extent be expected -since we have witnessed significant expansion over the past forty years.…”
Section: Introductionmentioning
confidence: 91%
“…Thus, a software process ontological framework could enable users of one software development process lifecycle to interact more smoothly with those using a different software development approach, while at the same time allowing all software developers to examine and clarify their own use of terminology and language. In previously published related work [4], the authors have elaborated on some examples of inconsistent terminology in the software process domain (refer to Figure 1). In this paper, we provide some additional information on how ontologies are constructed and utilised, while also providing a brief overview of some of the present sources of software development process terminology, including books/bodies of knowledge, taxonomies and international standards.…”
Section: Fig 1 Software Terminology Landscape -A Process and Role Vmentioning
confidence: 99%